2020
DOI: 10.20473/jde.v5i1.18814
|View full text |Cite
|
Sign up to set email alerts
|

Determinants of Real Exchange Rate: A Behavioural and Fundamental Dynamic Analysis in Latin American Countries

Abstract: In this research, we analyze the determinants of the real exchange rate through the fundamentals and behavioral factors, adding other variables as monetary aggregates, economic growth, domestic savings, and productivity. We worked with thirteen Latin American countries from 1980 to 2018 and we used three estimates such as fixed-effects, random-effects, and System GMM. The findings show that although the real exchange rate has a large random component, due to the high coefficient presented by the past values of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 65 publications
0
2
0
Order By: Relevance
“…Several related empirical studies conducted in various developing countries such as the research of Chavez (2020), found that GDP growth had a positive effect on the exchange rate while the term of trade had a negative effect on the real exchange rate in Latin American countries. Almaw's research (2020) found that inflation, economic growth, money supply and government spending positively affect the exchange rate in Ethiopia while the trade ratio has a negative effect on the exchange rate in Ethiopia.…”
Section: Introductionmentioning
confidence: 99%
“…Several related empirical studies conducted in various developing countries such as the research of Chavez (2020), found that GDP growth had a positive effect on the exchange rate while the term of trade had a negative effect on the real exchange rate in Latin American countries. Almaw's research (2020) found that inflation, economic growth, money supply and government spending positively affect the exchange rate in Ethiopia while the trade ratio has a negative effect on the exchange rate in Ethiopia.…”
Section: Introductionmentioning
confidence: 99%
“…The banking sector performance report in the second quarter of 2015 showed an increase in the ratio of bad loans or NPL. The weakening condition of the rupiah was exacerbated by the high interest rates and high inflation, causing one of them to increase the NPL at that time (Chavez, 2020).…”
Section: Introductionmentioning
confidence: 99%